Sociological worlds : comparative and historical readings on society / edited by Stephen K. Sanderson. - Sanderson, Stephen K. (Routledge, 2013)
'Sociological Worlds' attempts to present a comprehensive picture of human social life - from the perspective of the comparative-historical revolution in sociology and presents some of the best theoretical and empirical work that is now being done by comparative-historical sociologists, as well as work by their close cousins, socio-cultural anthropologists. From this perspective, readers gain a picture of the major ways in which human societies differ.